Transcriptome analysis of purple and green Apostichopus japonicus reared under different breeding environments - Liu, Bohong; Xing, Lili; Liu, Shilin; Sun, Lina; Su, Fang; Cui, Wei; Jiang, Chunxi (Frontiers in Marine Science, 2024)
Sea cucumber (Apostichopus japonicus) is one of the cultured species with the highest production value to a single species in China's marine agricultural industry with high nutritional and medicinal value. Body color influences numerous biological functions in sea cucumbers, and it has become a key trait in selective breeding. It is found that a cultivation environment with strong light intensity leads to a lighter body color of A. japonicus compared to dark conditions. However, little research has been conducted on the molecular mechanisms regulating body color in different breeding environments. In this study, we used Illumina sequencing to examine gene expression patterns in green and purple A. japonicus exposed to different culture conditions. Overall, the genes in the body wall of purple individuals were more affected by the environment. We also identified pathways that were potentially influenced by the breeding environment, such as "Drug metabolism -cytochrome P450", "Porphyrin and chlorophyll metabolism", "Phosphatidylinositol signaling system", "TGFbeta signaling", and "mTOR signaling". The aim of this study was to determine the light conditions and breeding environment that are more favorable to the requirements of body color in A. japonicus and apply them to the selection of high-quality breeds. The results obtained will support the breeding of A. japonicus with specific traits and the production of seedlings to promote the development of this maricultural industry.